El pliego de condiciones electrónico en la contratación pública - Romero-Pérez, Jorge Enrique (2014)
The standard and mandatory of clauses constitutes the rules that the contracting parties should complete. It is the negocial proposal of the State that the potential offerers can refute or to try to modifity